THE CONNECTION OF THE MAIN CONDITIONS OF THE POPULATION'S WELL-BEING WITH BUSINESS ACTIVITY (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article deals with the effective organisation and development of entrepreneurial activity in a market economy, providing the basic conditions for the well-being of the population in society and achieving its high level.